Sodium-Glucose Cotransporter-2 Inhibitor Use and Outcomes Following Transcatheter Aortic Valve Replacement: A Propensity-Score Matched Analysis - Hritvik Jain; Dhiran Verghese; Jyoti Jain; Ramez M Odat; Ignacio Inglessis-Azuaje; Dhaval Kolte; Paul C Gordon; J Dawn Abbott; Saraschandra Vallabhajosyula (Critical Pathways in Cardiology: A Journal of Evidence-Based Medicine, 2026)
Background: Sodium-glucose cotransporter-2 inhibitors (SGLT2i) have been shown to improve outcomes across all heart failure (HF) phenotypes, but their role in patients undergoing transcatheter aortic valve replacement (TAVR) remains limited. Methods: Using the TriNetX Global Collaborative Network, we identified all adults undergoing TAVR (2019–2025). Patients were divided into 2 groups - those receiving SGLT2i within 1-year post-TAVR and matched controls not receiving SGLT2i. Propensity-score matching was applied across demographics, comorbidities, medications, and labs. The primary endpoint was a composite of all-cause mortality and HF exacerbation. Secondary outcomes included major adverse cardiac and cerebrovascular events, ischemic stroke, acute myocardial infarction, and all-cause rehospitalization at 1 and 5 years. Results: Among 55,147 TAVR patients, 2,478 (4.5%) received SGLT2i. After 1:1 matching, 2,020 well-balanced patients per group were analyzed. At 1 year, SGLT2i use was associated with lower incidence of primary composite endpoint (hazard ratio [HR] 0.74, 95% confidence interval [CI] 0.69–0.80), HF exacerbation (HR 0.44, 95% CI 0.31–0.62), and all-cause rehospitalization (HR 0.41, 95% CI 0.38–0.44). Benefits persisted at 5 years with additional reduction in all-cause mortality (HR 0.84, 95% CI 0.73–0.97). Acute pancreatitis (falsification outcome) showed no association at both follow-ups. Conclusions: In a large multinational database, SGLT2i therapy after TAVR resulted in a significantly lower incidence of all-cause mortality or HF exacerbation.